(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Recently, there have been discussions about the development of educational programs, but each university, despite the generally recognized rules, has its own vision and in the process of educational activity tries to answer the question of what the OP should be, the implementation of which it ensures and what is its peculiarity. The purpose of the article It consists in highlighting one’s own experience in developing, implementing and revising OP Marketing, taking into account the regional aspect of the university in which it is implemented. reasonably highlight the peculiarity of building a student-centered educational program taking into account the regional aspect. Methods. The proposed model of the development, implementation and implementation of OP Marketing, which is based on the analysis of program documents of authorities at the regional level, as well as the results of our own empirical research through a survey, allows us to reasonably highlight the peculiarity of building a student-centered educational program taking into account the regional aspect. Results. The article adapts the Tuning methodology to the construction of a model for the development, implementation and implementation of OP Marketing for the first (undergraduate) level at the Lesia Ukrainka University, taking into account the regional context. The proposals of employers, education seekers who took part in the public discussion of the OP and in the course of a direct meeting with stakeholders were determined. The profile and purpose of OP Marketing in the context of future employment has been formed. A methodology for assessing the quality of OP was developed with the aim of improving it. The importance of conducting surveys on the quality of OP was noted. Conclusions. The formation of OP becomes a collective matter not only of the OP support group or the department of marketing, but of the entire university through its structural units. The obtained results can be used by guarantors of OP Marketing of the first (bachelor) level during preparation for accreditation in the course of writing self-assessment information.